African traditional widowhood rites and their benefits and/or detrimental effects on widows in a context of African Christianity - Manala, Matsobane (HTS teologiese studies, 2015)
Traditional Africans teach ubuntu principles of communality, mutual respect, caring and so forth, but they do not walk the talk with regard to the treatment of widows. In the footsteps of Jesus of Nazareth, Christian communities preach unconditional love, especially for the poor, marginalised and vulnerable. Implementation is, however, grossly lacking in respect of the treatment of widows. There is thus an apparent deliberate uncaring, disrespectful, discriminatory, impolite and unjust treatment of widows in African communities in spite of the ubuntu values and Christian teaching that emphasise love and caring, especially towards the grieving and thus vulnerable widows. Widows seem to be neglected and even oppressed in our time. The aim of this research is to critically examine African traditional widowhood rites and practices with special reference to the comfort or pain to which they subject African widows. The research further aims to examine the behaviour of some African Christians belonging to three congregations of one mainline church to determine whether their treatment of widows resonates with Jesus’ teaching regarding the requisite care of widows. The issue of widowhood in Africa, in terms of the apparent plight of these bereaved and grieving women, needs to be urgently addressed for change in the 21st century. A critical literature study of relevant sources and a newspaper article will be used for this research. My personal experiences and continuing observation as an insider will also inform the research in useful ways.